Removal of sulfadimethoxine antibiotic from aqueous solutions using carbon nanotubes - Abolfazl Rahmani Sani; Ahmad Hosseini-Bandehgharaei; Mahsa Naeemi; Ameneh Navidzadeh; elham agheli (Mashhad University of Medical Sciences, 2018)
Abstract Background and aim: Antibiotics are a category of organic pollutants that can cause serious environmental problems through their disposal and uncontrolled release to the environment. The purpose of this study was to investigate the removal of sulfadimethoxine from aqueous solutions using carbon nanotubes. Materials and Methods: The present work was an experimental study in which the effects of different parameters, such as PH, time, doses of carbon nanotubes, and different concentrations of sulfadimethoxine, on the removal of antibiotic from solutions were examined. All experiments were carried out in a 100-mL reactor at laboratory temperature (24 ± 2 ° C) using a magnetic stirrer at 350 rpm. Results: The results showed that the maximum removal efficiency (94.5%) was occurred at pH = 6, adsorbent dosage 0.04 g, contact time of 30 min, and initial concentration of 20 mg/L. The findings on the effect of pH showed that the adsorption capacity increases with increasing pH, and at pH = 6, it reaches its maximum and then decreases again. The extent of removal was increased by increasing the dose of carbon nanotubes and the optimum amount for initial concentration of 100 mg/L (50 mL) was 0.04 g. The amount of absorption increased with increasing contact time and the maximum absorption occurred when the contact time was 30 min. The sulfadimethoxine antibiotic isotherm followed the Langmuir isotherm model (R2 = 0.9800) and the pseudo-second-order kinetic model (R2 = 0.9937). Conclusion: The results showed that carbon nanotubes have a high potential for removal of sulfadimethoxine from aqueous solutions, due to its properties like its high surface area.